Capital Structure, Financial Performance, and Macroeconomic Conditions: Evidence From Indonesia Stock Exchange - Sukma Febrianti; Mustaruddin Mustaruddin; Nur Afifah (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2024)
his study aims to analyze the influence of capital structure, financial performance, and macroeconomic conditions on firm value (Tobin's Q) in companies included in the Kompas 100 index (100 companies with good liquidity and large market capitalization) listed on the Indonesia Stock Exchange between 2018 and 2022. A total of 50 companies with historical data for 5 years were analyzed amounting to 250 observational data. The data analysis method used is panel data regression analysis processed using Eviews software version 10. The results show that financial performance has a significant positive effect on firm value, and capital structure has a negative but not significant effect on firm value. Among the macroeconomic variables, inflation has a negative influence while interest rates have a positive influence, both of which are significant on firm value. However, GDP growth shows an influence that is not significant towards changes in firm value. The determinants of firm value are very complex thus each company needs to identify the key factors influencing them. It is recommended for further research to include corporate governance and firm growth variables.